Levamisole as an immunomodulator to ameliorate vaccination stress in crossbred bulls - RAO, T K S; MOHANTY, T K; BHAKAT, M (The Indian Journal of Animal Sciences, 2017)
Present study was planned on 8 crossbred bulls (144 ejaculates) to study effect of levamisole on vaccination stress. All the bulls were vaccinated with Trio-vac vaccine as per routine schedule of the farm. In treatment group (4 bulls) levamisole was injected 1 week prior to vaccination, whereas in control normal saline was injected. Semen ejaculates were evaluated during pre-vaccination (1 week) and post-vaccination (8 week) period. Results revealed significantly lesser reaction time, sperm abnormalities and higher sperm concentration (million/ml), total motile spermatozoa (×106), total live spermatozoa/ml (×106), total sperm (×106) and total dose harvested in treated group. Individual motility, mass motility, NEC, HOST and IA (%) was higher in levamisole treated group, but it was not statistically significant. Vaccination stress was evident in both group, however the stress was prominent in control. Level of serum Zn and immunoglobulin improved significantly in treated bulls. Levamisole treatment in vaccinated bulls has positive effect to some extent in amelioration of stress.